DETERMINATION OF AIR DEFENSE IDENTIFICATION ZONE (ADIZ) IN ORDER TO SUPPORT SOVEREIGNTY OF NATIONAL AIR REGION - Marsono, Marsono; D.A.R., Deni (Jurnal Pertahanan & Bela Negara, 2018)
One aspect of air spatial arrangement relating to national airspace sovereignty is to establish Air Defense Identification Zone (ADIZ) which established on the basis of security considerations, particularly for the purposes of foreign aircraft identification. ADIZ Indonesia that has been established at this time is not ideal because it is still above Java and surrounding areas, which is still not sufficient in the face of the vast territory of Indonesia. In order to do so, the purpose of this study is to analyze the current condition of ADIZ Indonesia, what efforts have been made to re-establish ADIZ Indonesia in order to suport sovereign national airspace, and the ADIZ stipulation provision in accordance with international air law. This research using qualitative method, data collected by interview and literature review. The results show that ADIZ Indonesia currently resides in the airspace of a small portion of South Sumatra, Java and Madura, Bali, Lombok and a small portion of the western Sumbawa Island, not outside the territorial sea territory (ZEE). Attempts to reassign ADIZ Indonesian terrritory has been implemented through discussion forums or FGDs held at BNPP, and the appointment of ADIZ Indonesia is already based on international customary law at that time. Â Keywords: ADIZ, aircraft identification, airspace sovereignty, air law One aspect of air spatial arrangement relating to national airspace sovereignty is to establish Air Defense Identification Zone (ADIZ) which established on the basis of security considerations, particularly for the purposes of foreign aircraft identification. ADIZ Indonesia that has been established at this time is not ideal because it is still above Java and surrounding areas, which is still not sufficient in the face of the vast territory of Indonesia. In order to do so, the purpose of this study is to analyze the current condition of ADIZ Indonesia, what efforts have been made to re-establish ADIZ Indonesia in order to suport sovereign national airspace, and the ADIZ stipulation provision in accordance with international air law. This research using qualitative method, data collected by interview and literature review. The results show that ADIZ Indonesia currently resides in the airspace of a small portion of South Sumatra, Java and Madura, Bali, Lombok and a small portion of the western Sumbawa Island, not outside the territorial sea territory (ZEE). Attempts to reassign ADIZ Indonesian terrritory has been implemented through discussion forums or FGDs held at BNPP, and the appointment of ADIZ Indonesia is already based on international customary law at that time.